ДУХОВНОЕ ЕДИНСТВО НАРОДА – ГАРАНТ СТАБИЛЬНОСТИ КАЗАХСТАНСКОГО ОБЩЕСТВА - Амантаева, А.Б. (My University, 2019)
Аннотация Духовное согласие – основа единства народа Казахстана» – это сердцевина всей внутренней политики нашей страны. В свою очередь, межэтническое и межконфессиональ- ное согласие строится на толерантности. Вопрос укрепления межэтнического согласия возник перед Казахстаном с первых шагов на пути независимого, суверенного развития. Го- сударственная независимость стала залогом безопасности и духовного благополучия мил- лионов казахстанцев. И Казахстан воспользовался этим историческим шансом в полной мере. Abstract Because today the scale reniece serogen the formation of moral,high quality and popular education, a special place in the upbringing of healthy generation. A patriot loves his country, high moral the owner, national education, education of the citizen to live in them the national spirit, that the wise he shows. Education of students in the course of employment associated with household traditions, applicable to the birth of a child scene tradition, legend, – the role of the ban, the ethics of welcome, respect, guests' expectations, ethics of eating, traditions, moral education, ethics and culture of speech, clothes, and a labor education national education, culture and national values of the Kazakh people, as well as their educational value advanced models outunit.
Spiritual unity of the people – the guarantor of stability of the Kazakhstan society
Keywords: Стабильность; духовность; единство; консенсус; толерантность; Stability; consent; unity; consensus; sovereignty